2015
DOI: 10.1007/s12275-015-5046-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus salivarius Ren on cancer prevention and intestinal microbiota in 1, 2-dimethylhydrazine-induced rat model

Abstract: Probiotics have been suggested as a prophylactic measure in colon cancer. The aim of this study was to investigate the impact of Lactobacillus salivarius Ren (Ren) in modulating colonic microbiota structure and colon cancer incidence in a rat model after injection with 1,2-dimethyl hydrazine (DMH). The results indicated that oral administration of Ren could effectively suppress DMH-induced colonic carcinogenesis. A significant decrease in cancer incidence (87.5% to 25%) was detected in rats fed with a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…These findings suggested that Ren is a potential agent for colon cancer prevention (Zhang et al . ). Lastly, Zhu et al .…”
Section: Probiotic Status Of L Salivarius: Results From Animal Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings suggested that Ren is a potential agent for colon cancer prevention (Zhang et al . ). Lastly, Zhu et al .…”
Section: Probiotic Status Of L Salivarius: Results From Animal Modelmentioning
confidence: 97%
“…Administration of Ren reduced the amount of Ruminococcus, Clostridiales bacteria and Bacteroides dorei, and increased the amount of Prevotella. These findings suggested that Ren is a potential agent for colon cancer prevention (Zhang et al 2015). Lastly, Zhu et al (2014) found that Ren prevents early colorectal carcinogenesis in a DMHinduced rat model.…”
Section: Cancer and Carcinogenesismentioning
confidence: 86%
“…These results showed a lot of different indicators of the effects of probiotics on meat quality (Suo et al, 2012). Zhang et al (2015) considered that the shear force of raw drumstick decreased in the whole yeast treatment relative to the controls. Zhou et al (2010) demonstrated that B. coagulans probiotic affected meat quality by decreasing the drip loss of broiler breast meats of Guangxi Yellow chickens.…”
Section: Isolation and Probiotic Potential Of Lactobacillus Salivariumentioning
confidence: 96%
“…Increasing evidence indicates that Lactobacillus and Pediococcus strains exert beneficial effects by a variety of complementary mechanisms, including an ability to modulate host immune function, high adhesion capacity, cancerpreventing attributes, reduction of serum cholesterol levels, high antimicrobial activity against pathogens, and normalization of the microbiota composition (Okamoto et al, 2007;Noujaim et al, 2009; Isolation and Probiotic Potential of Lactobacillus salivarius and Pediococcus pentosaceus in Specific Pathogen Free Chickens Meng et al, 2010;Zhang et al, 2011;Kiran et al, 2015;Xie et al, 2015;Zhang et al, 2015). Promising probiotic strains should have some superior biological properties, especially improving growth performance, intestinal microbiota balance, and meat quality, and decreasing noxious gas emission (Meng et al, 2010;Fan et al, 2013;Jeong et al, 2014;Peng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation